(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The research aimed at investigating the effects of Lead as Pb2+ ion on growth of tomato (Lycopersicon esculentum M.). The study comprised two phases, in vitro and field experiment. The concentration of lead treatment applied to in vitro, and field base experiment were 0ppm, 50ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, and 400ppm with four replications each. The parameters investigated include percentage germination, radicle length, plumule length, plant height, fresh weight, dry weight, root length and number of leaves. The results showed action of Pb2+ ion increase percentage germination while radicle and plumule length, fresh weight, dry weight, number of leaves, and root length significantly decreased at high concentration of Pb2+ ion compared to controls. Moreover, plants height revealed stunted growth. Conclusively, actions of Pb2+ ion at high concentration revealed decreased in plant activities associated with tomato growth.